Age changes in some linear measurements and secular trend in height in adult Indian women - Bagga, Amrita (Acta Biologica Szegediensis, 2013)
Decline in linear body dimensions with age has been reported in studies throughout the world. There is sufficient evidence that a portion of the changes in stature in a cross-sectional study may be due to secular trend rather than ageing. In the present study, age changes in linear measurements were studied and an attempt made to partition the age associated decline in stature from that of secular trend in height in younger generation. Data comprised of 126 Maratha women patients living in Government Mental Hospital in Pune, India. Their age ranged from 30 to 70 years. Using stature and sitting height, sub-ischial height was derived for each subject which was used as an indirect measurement to approximate the secular trend in height gain in younger generation. Iliac height- a direct measurement was used to quantify the increase in height in younger cohorts. Analysis showed that almost 71 percent (2.55cms) of statural difference between youngest and oldest age group could be attributed to ageing effect, and remaining 29 percent (1.05cms) to secular trend in those born later in time. The timing of reduction in height appears to be in the fifth decade accelerating in subsequent decades.